The Tourism Area Life Cycle Concept in Identifying the Characteristics of the Alas Purwo Banyuwangi National Park - Ayu Wanda Febrian; Zulfatun Nikmah; Chornela Dinda Palupi; Indie Birrul Halida; Citra Alfitri Zahra; Ervilian Suci Desika; Rika Setiya Ayu; Christandy Yervianto (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2023)
Purpose: This research aims to comprehensively understand, evaluate, and categorize the life cycle of tourism areas. Method: Employing a descriptive-qualitative approach, this study conducted interviews with multiple managers and engaged in direct observations. Through both primary and secondary data collection methods, the distinctive features of the Tourism Area Life Cycle (TALC) were identified and categorized. Results: The findings reveal that rejuvenation is essential for all eight components of the tourism area life cycle within Alas Purwo National Park. These TALC components exert a significant influence on the developmental stage of the park. The research presents a range of opportunities and challenges in managing tourist attractions within the park. These challenges present opportunities for managing attractions more effectively. Strategies for expansion involve the addition of artificial attractions and enhancements to facilities. A focal point in the development of Alas Purwo National Park is the engagement of the local community and visitors, facilitated by raising their awareness of sustainable tourism practices. Contribution: This article serves as a valuable resource for information, reference, and initial exploration, thus enriching the broader community's comprehension of the life cycle within Alas Purwo National Park. Furthermore, it offers insights into the behaviors and awareness of tourists. It provides managerial assistance in categorizing the distinct characteristics of tourism within the park.